TINJAUAN HUKUM ISLAM TERHADAP ALTERNATIF PENYELESAIAN SENGKETA DI LUAR PENGADILAN SECARA MEDIASI DALAM SENGKETA HARTA WARIS: (Di Desa Bantunan Kecamatan Pajar Bulan Kabupaten Lahat) - Risdianto (Irtifaq, 2021)
In the distribution of inheritance, it has been regulated in such a way in the provisions of Islamic law and positive law, where anyone is entitled to receive the inheritance, and who is not entitled to receive the inheritance, then about how many rights must be given to the heirs of the treasure left by the deceased. But the problem is, even though it is regulated in such a way in the existing regulations, there are still frequent conflicts/disputes in the distribution. One of the heirs has bad intentions, for example, wants to control all the inheritance of the deceased. By using a qualitative approach, this type of field research, data from observations, interviews and documentation are analyzed deductively by taking theories or arguments / legal rules related to the distribution of inheritance which are settled out of court, then from the theory drawn to the facts or facts of cases in the field. Then the results of the study indicate that the settlement of disputes outside the court through mediation in inheritance disputes in Bantunan Village, Pajar Bulan District, Lahat Regency, South Sumatra Province, in its implementation is not in accordance with applicable legal rules, both Islamic law and positive law.Keywords: Islamic Law, Inheritance, Mediation